Community biodiversity management : promoting resilience and the conservation of plant genetic resources - Boef, Walter de. (Issues in agricultural biodiversity., 2013)
"The conservation and sustainable use of biodiversity in the environments where this diversity originated or is being used, are issues which are high on the policy agenda. This book is the first to set out a clear overview of community biodiversity management (CBM) as an approach to meet social, economic and environmental change"--